Fastness properties of colorant extracted from locust beans fruits pods to dye cotton and silk fabrics - Ibrahim Abdullahi Umar; Mohammed Najib bn Muh’d nor; Wong Yee Ching (2013)
This study investigates the extraction of colour from locust beans fruits pods to dye cotton and silk fabrics using the mordanting treatment with these mordants of CUSO4, FERROUS (II) & (III) SULPHATE AND ALUM. Aqueous and solvent extraction method was adopted for this experiment. The colour obtained was different shades ranging from soft, light brown and brown, depending on the mordant used. However, the change in colour can be improved using other mordant from the ones used in this study, fastness properties test was carried out and proved good result. Therefore, the findings will benefit local dyers, farmers, textiles industries; organisations, institutions that deal with dyes/colour, research institutes and can be good for future research on other natural fabrics.